Winter management for steer calves on a wintering, grazing, and fattening program. - Smith, E.F.; Koch, B.A.; Walker, G.L.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
A previous test has been reported in Circular 349 from this station. The objective of the study is to determine if winter bluestem pasture can be supplemented in such a manner that calves wintered on it will compare favorably in yearly performance with steer calves wintered on good quality roughage. It was noted in the first test that production costs were cheaper on winter grass and that calves wintered in the drylot would have to grade higher as fat cattle and sell for more per cwt. to make as great a return as those wintered on pasture.
Keywords: Beef; Gain; Grazing; Wintering